Pengaruh Corporate Governance terhadap Nilai Perusahaan (Tobins 'Q) pada Perusahaan Manufaktur yang Listing di Bursa Efek Indonesia - Desmiza Desmiza (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
One of the company's performance indicators is Tobins'Q, therefore it is important for the company to manage it effectively and efficiently. Tobins'Q can be influenced by both internal and external factors of the company. The purpose of this study is to investigate the effect of the corporate governance structure as proxied by institutional ownership, independent commissioners, and the number of commissioners on firm value (Tobin's Q). The method used is descriptive and verification method, using multiple panel data regression analysis tools with eviews 10 program, the results of the study prove that institutional ownership, independent commissioners and the number of members of the board of commissioners significantly affect Tobin's Q. However, for the variable number of board of commissioners an anomaly occurs. where the results contradict the hypothesis.